Water quality of submarine caves and marine karst lakes in Cat Ba Archipelago (Hai Phong, Vietnam) - Cao, Thi Thu Trang; Nguyen, Dang Ngai; Le, Van Nam; Pham, Thi Kha; Dinh , Hai Ngoc; Tran, Manh Ha; Nguyen, Van Minh; Dau, Van Thao (Vietnam Journal of Marine Science and Technology, 2025)
Submarine caves and marine karst lakes in the Cat Ba archipelago (Hai Phong) were surveyed in June and November, 2019. The results showed that the water was weakly alkaline, the dissolved oxygen concentration was very low, most of the oxygen saturation in the water was in the range of 50–70%. Water in submarine caves had higher and more stable salinity than that in marine karst lakes, however, the dissolved oxygen concentration was lower than that in lakes. The self-purification of water was better in the rainy season. The water was polluted by ammonium in the rainy season in Ang Vem, Ba Man, Ba Mat and Ang Gay lakes. There is no evidence of organic contamination but the high nitrate and phosphate concentration had been recorded. The presence of H2S gas in the water had begun to affect organisms.